Pendidikan Karakter Melalui Sains - Chusnani, Diana (Jurnal Kebijakan dan Pengembangan Pendidikan, 2013)
Some of the problems and conflicts that arise in social life due to the lack of strong character. Students and school leavers often face problems in life, which caused less strong character. Communities are now beginning to question the education system which assessed student has not managed to strengthen character. On the other side of the school is also facing difficulties in implementing character education. This study is an idea that is expected to provide solutions to the implementation of character education through science learning. This study does not propose character education as a stand-alone subject tetapui character education messages through methods of science learning with hands-on and minds-on is considered strongly supports strengthening the character of students. Learning science students have the right to direct the character's curiosity, to think logically, critically and creatively innovative, honest, healthy living, self-confidence, respect for diversity, discipline, self-reliant, responsible, caring environment and love of science.